Hantavirus in humans: a review of clinical aspects and management - Vial, Pablo A; Ferrés, Marcela; Vial, Cecilia; Klingström, Jonas; Ahlm, Clas; López, René; Le Corre, Nicole; Mertz, Gregory J (The Lancet infectious diseases, 2023)
Hantavirus infections are part of the broad group of viral haemorrhagic fevers. They are also recognised as a distinct model of an emergent zoonotic infection with a global distribution. Many factors influence their epidemiology and transmission, such as climate, environment, social development, ecology of rodent hosts, and human behaviour in endemic regions. Transmission to humans occurs by exposure to infected rodents in endemic areas; however, Andes hantavirus is unique in that it can be transmitted from person to person. As hantaviruses target endothelial cells, they can affect diverse organ systems; increased vascular permeability is central to pathogenesis. The main clinical syndromes associated with hantaviruses are haemorrhagic fever with renal syndrome (HFRS), which is endemic in Europe and Asia, and hantavirus cardiopulmonary syndrome (HCPS), which is endemic in the Americas. HCPS and HFRS are separate clinical entities, but they share several features and have many overlapping symptoms, signs, and pathogenic alterations. For HCPS in particular, clinical outcomes are highly associated with early clinical suspicion, access to rapid diagnostic testing or algorithms for presumptive diagnosis, and prompt transfer to a facility with critical care units. No specific effective antiviral treatment is available.